2003
DOI: 10.2169/internalmedicine.42.318
|View full text |Cite
|
Sign up to set email alerts
|

Metronidazole Plus Ciprofloxacin Therapy for Active Crohn's Disease

Abstract: Objective The aim of this study was to investigate the efficacy of metronidazole plus ciprofloxacin for the treatment of Japanese patients with active Crohn's disease. Methods and Patients Seven patients (counting one patient twice with 2 enrollments at a 5-month interval) with a flare-up of Crohn's disease were enrolled. While continuing the baseline treatment under which the patients relapsed, they received metronidazole 250 mg twice (4 patients) or three times (3 patients) daily plus ciprofloxacin 200 mg th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 12 publications
1
11
0
Order By: Relevance
“…These antibiotics are used in clinical practice for controlling symptoms and preventing septic complications in patients with active CD [24, 31]. They are known to alter the bacterial composition of the intestine by changing the balance between different bacterial groups [32, 33].…”
Section: Introductionmentioning
confidence: 99%
“…These antibiotics are used in clinical practice for controlling symptoms and preventing septic complications in patients with active CD [24, 31]. They are known to alter the bacterial composition of the intestine by changing the balance between different bacterial groups [32, 33].…”
Section: Introductionmentioning
confidence: 99%
“…An uncontrolled trial (22) indicated that cipro in combination with metro was well-tolerated and beneficial for achieving clinical remission for patients with active CD, particularly when there was involvement of the colon. A study (23) in Japan found that combination therapy of cipro and metro for four weeks significantly decreased the C-reactive protein in all the patients involved. In a randomized non-placebo controlled trial (24) involving 40 CD patients, complete remission was observed in 56% patients treated with cipro and 55% patients treated with mesalazine.…”
Section: Discussionmentioning
confidence: 99%
“…75 Indeed, induction of clinical remission of CD with antibiotics has yielded mixed findings in a number of independent studies, with only a small number of studies demonstrating significant differences between antibiotics and placebo (Table 3); again, these studies all had differences in duration of treatment (from 4 weeks to 6 months), with different antibiotics used in a number of combinations. [76][77][78][79][80][81][82][83][84][85] Results of a retrospective study of patients receiving the nonsystemic antibiotic rifaximin, both in traditional and extended intestinal release forms, showed that rifaximin induced remission and response compared with placebo. 83,84,86 In contrast with systemic antibiotics, which are associated with a greater percentage of AEs than placebo (eg, abdominal pain, nausea, vomiting, vaginal candidiasis, dizziness, and taste disturbance), [77][78][79]81 rifaximin had fewer disturbances mostly limited to the GI tract (eg, nausea, flatulence).…”
Section: Remission Of CDmentioning
confidence: 99%